Hengsberg/Zlatten, Österreich: Siedlungen und Metalldeponierungen der Urnenfelder- und frühen Hallstattzeit in den Südostalpen - Neumann, Daniel (e-Forschungsberichte des DAI, 2023)
This small project at the RGK Frankfurt was initiated to strengthen research on the Urnfield Culture in the Southeastern Alps with a special emphasis on the ritual use of space as well as settlement archaeology. Within the framework of the project the archaeological findings of two sites will be prepared for publication.